Analisis Penerapan Pendekatan Saintifik dalam Pembelajaran Bahasa Indonesia pada Teks Deskripsi di SMPN 3 Maja - Dini Andriyani; Rochmat Tri Sudrajat; Yusep Ahmadi F (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Learning innovation in today's curriculum plays a vital role for more creative learning. One of the tools of innovation is through an approach or learning strategy. One of them is the application of a scientific approach which requires students to be active, critical and communicative. Thus, how does scientific approach work in text description at SMPN 3 Maja. The goal in this research is to analyze the achievement of success in implementing learning innovation, which is with scientific approach in text description at SMPN 3 Maja. The method for knowing the success of implement this innovation is descriptive qualitative by analyzing after learning with a scientific approach in the description text. Indonesian is a study that requires student to study many texts, one of which is a description text. The application of scientific approach to Indonesian study in the description text at SMPN 3 Maja after analyzing is difficult to apply because the student’s character that still belongs to the teacher, lacking the breeding of active and critical learning making a student has a strong passive character and tend to be difficult for self-study, and for introver student makes application of scientific approach not communicative. Therefore, scientific approach can be applied if the active character of student plays a role. The importance  of applying scientific approach support effectiveness in participation of student activation.